Overexpressed transferrin receptor implied poor prognosis and relapse in gastrointestinal stromal tumors - Zhuang, Chun; Li, Xiaoqi; Yang, Linxi; Ma, Xinli; Shen, Yanying; Huang, Chen; Pan, Tao; Cui, Jianzhi; Ni, Bo; Wang, Ming (Frontiers in Oncology, 2023)
Ferroptosis, as a novel-induced programmed cell death, play critical roles in the pathogenesis of cancers. However, the promising biomarkers of ferroptosis in GIST remain to be elucidated. Herein, the expression of ferroptosis-related genes was analyzed in GIST.Among the 64 ferroptosis-related genes, Transferrin Receptor (TFRC) expression presented a remarkable upregulation in high-risk patients through GEO dataset analysis, as well as its significant change after imatinib treated. KEGG pathway enrichment analysis of TFRC-relevant genes revealed that TFRC expression was closely associated with cell growth pathways and metabolism-related pathways. Furthermore, patients with high-risk degree and recurrence were more likely to exhibit high TFRC expression by immunohistochemistry. Additionally, high TFRC expression indicated an undesirable state of patients' relapse, which could be serve as a powerful significant independent predictor of RFS. In summary, we systematically summarize the expression characteristics and clinical relevance of TFRC and show that TFRC can be used as a prognostic factor, which can be considered as potential therapeutic targets in GIST.